Aligner-mediated cleavage of nucleic acids and its application to isothermal exponential amplification. Issue 11 (28th February 2018) - Wu, Wanghua; Zhang, Tao; Han, Da; Fan, Hongliang; Zhu, Guizhi; Ding, Xiong; Wu, Cuichen; You, Mingxu; Qiu, Liping; Li, Juan; Zhang, Liqin; Lian, Xiang; et al.
Abstract : A programmable sequence-specific aligner-mediated cleavage endows strand displacement amplification with excellent universality, high sensitivity, high specificity and simple primer design. Abstract : We herein describe a simple and versatile approach to use conventional nicking endonuclease (NEase) for programmable sequence-specific cleavage of DNA, termed aligner-mediated cleavage (AMC), and its application to DNA isothermal exponential amplification (AMC-based strand displacement amplification, AMC-SDA). AMC uses a hairpin-shaped DNA aligner (DA) that contains a recognition site in its stem and two side arms complementary to target DNA. Thus, it enables the loading of an NEase on DA's stem, localization to a specific locus through hybridization of the side arms with target DNA, and cleavage thereof. By using just one NEase, it is easy to make a break at any specific locus and tune the cleavage site to the single-nucleotide scale. This capability also endows the proposed AMC-SDA with excellent universality, since the cleavage of target DNA, followed by a polymerase-catalyzed extension along a particular primer as a key step for initiating SDA, no longer relies on any special sequence. Moreover, this manner of initiation facilitates the adoption of 3′-terminated primers, thus making AMC-SDA highly sensitive and highly specific, as well as simple primer design.